Feminist theory(s) and history(s) of the present time: intersectionality, subalternity and decoloniality (Tempo e Argumento, 2021)
The aim of this article is to (re)think the history(s) of the present time in the light of the feminist theories that, through the concepts of intersectionality, subalternity and decoloniality, offer a view that is at the same time fruitful and renewed. At the heart of the approach, the idea of detouring/submerging the hegemonic, totalizing and / or dominant views, in order to clarify, a contrario, the plurality of existence(s)/experience(s) and practical, theoretical and symbolic modalities of their multiple expression(s) through pluri-interpretation(s)/reflection(s) thought horizontally (at ground level, it can be said) and not hierarchical. Here a multifocal view of polymorphic segments, diffuse traits and fragmentary narratives would emerge, forming a body-unity not by a fixing categorization-hierarchization, but by changeable juxtaposition-cohabitation, proposing a truly human and universal view.Keywords: feminist theories; intersectionality; subalternity; decoloniality; feminicide/ecocide.